The Impact of Genetic Polymorphisms in (STIM1 and ORAI1) on Erythropoietin Resistance in Patients with Chronic Renal Failure on Hemodialysis in Iraq - Alsabbagh , Farah f.; Mosa, Amal Umran; Abo Almaali , H.M.; Jafer, Hasanain Salah (Journal of Contemporary Medical Sciences, 2024)
Objective: This study aims to investigate the correlation between genetic polymorphisms in store-operated calcium channels (SOCs) signaling and resistance to erythropoietin treatment in patients with chronic renal failure (CRF). Anemia is a significant complication of CRF, and understanding the genetic factors contributing to resistance could provide insights into potential mechanisms influencing treatment outcomes. Specifically, the focus is on exploring the relationship between SOCs, a pathway activated by erythropoietin, and resistance to address the challenges associated with anemia in CRF patients. Methods: In this study, a single nucleotide polymorphism in each STIM1 and ORAI1 gene was selected. Genotyping was done by using allele specific polymerase chain reaction technique and the data was analyzed through the Statistical Package for the Social Sciences. 112 patients with CRF on hemodialysis were enrolled 58.9% of them were men and the mean age was 50.94±13.42. Results: We found that CC genotype of ORAI1 gene has a higher hemoglobin level, AA genotype of STIM1 has a higher EPO level, the interaction of the two genes showed that CCGG group has a higher Hb level and is considered good responder but represents only 4.5% of the patients Conclusion: After all the genetic polymorphisms of SOCs genes ORAI1 and STIM1 have no significant impact on erythropoietin resistance in patients with CRF on hemodialysis in Iraq.